Fatigue cracking of aluminium alloy AlZn6Mg0.8Zr subjected to thermomechanical treatment (Fracture and Structural Integrity, 2015)
The paper presents the results of experimental test of the fatigue of aluminium alloy type AlZn6Mg0,8Zr exposed to various low temperature thermomechanical treatment. Basquin’s characteristics of fatigue have been determined in mechanical test on smooth specimens at a simple state of loading in conditions of alternating bending. The tests were carried out on a fatigue test stand constructed by the authors – MZGS 100. The development of fatigue cracking has been described based on metallographic and fractographic investigations of the fractured samples making use of a scanning electron microscope (SEM). The results of qualitative microfractography of the tested samples in the low-cycle temporal range of fatigue strength revealed fractures of the transcrystalline quasi-cleavage type. It has also been found that local effects of intercrystalline brittle cracking of this type do occur.
Keywords: Aluminium alloy; Thermomechanical treatment; Fatigue cracking; SEM